Sinonim, Repetisi, dan Antonim dalam Bahasa Jepang: Telaah Majalah Nihongo Journal dan Hiragana Times - Rita Susanti; Siti Aminah; Nani Oktaviani (Lingua Cultura, 2009)
Purpose of this article is to know the kinds of repetition, synonym, and antonym in Japanese. Data were taken from the columns of “NJ News” of Nihongo Journal magazine to analyze the repetition and columns of “Tips for Livings in Japan” in Hiragana’s Times magazine, to discuss the synonym and antonym. The research result indicates that the full repetition is often used to emphasize information; then the context synonym is used in order to create a variation of sentences. Yet, there was also information was not found in the data, which was the antonym of kobutsu no kankei because it did not explain about family.